Aspek -Aspek Lingkungan Ramah Pembelajaran Pada Sekolah Dasar Di Kabupaten Bungo - Della Raudatul Fitri; Randa Purnama Sari; Nesa Afrianti; Opi Andriani (Lembaga Pengembangan Kinerja Dosen, 2024)
This article aims to find out learning-friendly aspects for children with special needs at Bungo Regency Elementary Schools. This research uses a qualitative descriptive research method. Data collection techniques include: observation and interviews. The research subjects or informants were the school principal and class teacher/homeroom teacher. The results of the research show that: (1) in this case the principal as the highest decision holder in an institution greatly influences the sustainability of children with special needs who wish to attend Normal School. (2) There are many problematic factors that exist regarding the implementation of a learning-friendly environment in the 3 elementary schools discussed in this article. However, the most basic and very influencing factor is the problem of the school not having special counselors for children with special needs but they accept children with special needs at the school. (3) The efforts made by the school to overcome the problems faced are that the school must first find a teacher who can specifically guide children with special needs so that these children can catch up with other normal children.